Assessing the food safety management for bottled water processing premises in Dak Lak Province in 2018 - Le Thi, Chau; Tran Thi Tuyet, Hanh (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2020)
AbstractObjective: To assess food safety management for bottled water processing premises and affecting factors. Study design: this was a cross sectional study; applied both quantitative and qualitative methods. This study was implemented in Dak Lak Province in 2019. 105 documents of bottled water processing premises in Dak Lak 2018 and related stakeholders participated in this study.Results: the process of certifying premises that met food safety conditions in 2018 was 89.5% being appropriate; 81.0% were certified for food safety knowlegde; 76.9% premises violated food safety regulations and 100% of these violated premises received administrative fines.Affecting factors included: policies supporting staff working in the food safety sector was inappropriate, the monitoring and inspection activities were not frequent, human resource only achieved 84%, lack of offices, working places and equipment needed, and achieved budget was only accounted for 17.0% of the estimated.Conclusions: a number of bottled water processing premises did not maintain adequate food safety conditions after receiving the Certification. The food safety management activities at these premises did not meet requirements. Further investments were needed to improve the management food safety management at bottled water manufacturing premises in the coming years.
Keywords: Food safety management; bottled drinking water; processing premises; Dak Lak.